Wykorzystanie wskaźników finansowych w zarządzaniu - Zarzecki, Dariusz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Traditional ratio analysis is primarily designed to meet the informational needs of equity investors and creditors. The objective of ratio analysis is the comparative measurement of risk and return, facilitating optimal investment and credit decisions. Ratios are generally classified as debt (solvency), liquidity, profitability, activity, and market value indicators and are designed to measure different aspects of a firm's operating, investment, and financing decisions. Ratios, even when well specified, may suffer from lack of appropriate benchmark to indicate an optimal level. Using an industry average as the benchmark may be useful for intraindustry analysis but not for the interindustry analysis. Furthermore, even for intraindustry analysis, the benchmark may have limited usefulness if the whole industry or major firms in that industry are doing poorly. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 564-573